Ontologi Demokrasi - zulfirman zulfirman (Fakultas Hukum Universitas Islam Indonesia, 2006)
Conceptually, democratic ontology is universal, however in the implementation ofdemocratic ontology is mostly affecfed by the values ofthe tnith and also the attitude o fhuman being to the others in the society. Consequently, on the opearational level, democracy under the declarative and oftative perspective is easily changes. It tends to follow the normative language which relates to the meaning of the truth and attitude of the human being obeyedby a certain society.